Children of two seasons poems for young people - Saguisag, Lara.; Fucio, Hubert B. (Pasig Anvil, 2007)
"Children are always out soaked in summer sweat or dancing in monsoon rain. They play. They laugh. They bloom."--Back cover.
1. Two seasons -- By the canal -- Animal games -- Potato play -- Church -- Storm signal -- Black cloud mood -- 2. Frog rain -- Tarsier -- Carabao -- City sounds -- Ube ice cream -- Kamayan -- 3. Dinner at lola's -- Tomas, the calavit giraffe -- Lola's animal sounds -- Lola's laundry lecture -- Invention -- Siesta time at the beach house -- Grandma's dreams.
Keywords: Children's poetry, Philippine (English)